2014
DOI: 10.18632/oncotarget.2069
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of IL-23 (p19, p40) and IL-23R identifies nuclear expression of IL-23 p19 as a favorable prognostic factor in colorectal cancer: a retrospective multicenter study of 675 patients

Abstract: IL-23 is a heterodimeric cytokine involved in inflammatory diseases; its role in cancer progression is controversial. Here we analyse the expression of IL-23 subunits (p40 and p19) and IL-23R in colorectal cancer with regard to disease progression, clinical-pathological and molecular aspects. Immunohistochemistry for IL-23p19, IL-23p40, IL-23R and CD8 was performed on a multi-punch tissue microarray of 195 colorectal cancers (cohort 1), matched normal tissue, adenoma and lymph node metastases. Results were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…In uni-and multivariate analysis, high IL-23 expression was associated with poor survival. This result was consistent with the finding of increased IL-23 expression in the normal-carcinoma sequence [13][14][15] and suggested IL-23 expression as a prognostic predictor.…”
Section: Discussionsupporting
confidence: 91%
“…In uni-and multivariate analysis, high IL-23 expression was associated with poor survival. This result was consistent with the finding of increased IL-23 expression in the normal-carcinoma sequence [13][14][15] and suggested IL-23 expression as a prognostic predictor.…”
Section: Discussionsupporting
confidence: 91%
“…Both IL-23 and CXCL-13 may facilitate pro-tumor phenotypes through initiating tumorigenesis, increasing angiogenesis, 41 promoting metastasis 42 and reducing infiltration of CD8 + T cells 43 in colorectal and non-small cell lung carcinoma (NSCLC), and by maintaining self-renewability of ovarian cancer stem cells (OCSCs) within the tumor microenvironment. 44 In our analyses, we found a significant correlation between higher expression of the Th17 differentiation cytokine IL-23 with better OS, in line with a study by Wolf et al 45 We also found that higher expression of the chemokine CXCL-13 was also associated with better OS in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…IL-23 has also been shown to enhance the expression of IL-17, by either in vitro generated human Th17 or ex vivo isolated memory Th17 cells, whereas IL-23 also exerts an inhibitory effect on the IL-12-induced IFN-␥ responses in Th1 cells (Annunziato et al, 2007). Additionally, accumulating evidences suggest that both IL-23 and IL-17 are significantly upregulated in many tumors, such as hepatocellular carcinoma, non-small cell lung cancer, and colorectal cancer (Helbling et al, 2014;Xu et al, 2014;Zarogoulidis et al, 2014). Further, it has been reported that IL-23 signaling promotes tumor growth and progression, and development of a tumoral IL-17 response (Grivennikov et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Allergic rhinitis, which is a condition similar to common cold, could affect mental and learning capacities up to 30% (Global Allergy and Asthma European Network addresses the allergy and asthma epidemic) (Bousquet et al, 2009). AR is an inflammatory disease of the nasal mucosa induced by an immunoglobulin E (Helbling et al, 2014)-mediated reaction in allergen-sensitized individuals. It has been reported that numerous loci and candidate genes show an association with AR (Gaddam et al, 2012;Genuneit et al, 2009;Ibrahim et al, 2012;Tomazic et al, 2014).…”
Section: Introductionmentioning
confidence: 99%